Pengaruh Hypnobreastfeeding pada Ibu Hamil Trimester III terhadap Kecukupan Asi pada Bayid di Puskesmas Kahuripan Kecamatan Tawang Kota Tasikmalaya - Igna Siti Napilah; Yulia Herliani; Endang Astiriyani (stikes dharma husada bandung, 2018)
Breastfeeding is the process of giving breast milk to the newborn baby by the mother after childbirth. Several factors can inhibit the availability of breast milk, causing the baby not enough milk, one of which is the psychological factors of the mother. Hypnobreastfeeding can help mothers increase milk production and reduce lactation stress by implanting positive affirmations into the mind. This study aims to determine the effect of Hypnobreastfeeding on breast milk sufficiency in infants.This research uses quasi experiment design research design with posttest only control group design research. The population of 50 multigravida pregnant women in the working area of Puskesmas â€‹â€‹Kahuripan. Sampling technique that is total sampling with inclusion and exclusion criteria, consist of 25 people with Hypnobreastfeeding treatment, and 25 people as control group. Univariate and bivariate analysis using Mann Withney U Test.Adequacy of breast milk with sufficient category resulted in 52% in the intervention group and by 24% in the control group. Mann Withney U Test test results obtained results with (Ïvalue) 0.020 less than Î± (0.05) so that H0 rejected or there is influence hypnobreastfeeding on breast milk adequacy in infants.There is a hypnobreastfeeding effect on the adequacy of breast milk in infants. It is expected midwives continue to provide maximum services for the success of breastfeeding mothers especially by doing this Hypnobreastfeeding.